Integrated management of collar rot in apple caused by Phytophthora cactorum - and SHWETA SHARMA, I.M. SHARMA*, H.S. NEGI (Indian Phytopathology, 2014)
Evaluation of different combinations of in dividually effective management inputs viz., biocontrol agents, bio-resources and fungicides against collar rot (Phytophthora cactorum) in apple indicated that a combined application of Trichoderma harzianum-1 (TH1), Enterobacter aerogenes- 2 (EA-2) and metalaxyl MZ (0.25%) provided complete control when applied 7 days prior to inoculation under pot and 20 days before planting under nursery conditions, whereas under orchard conditions it increased the shoot length up to 32.2 cm as compared 6.1 cm in untreated plants. Next best treatments were an integrated application of T. viride-5 (TV5) + Bacillus subtilis 11 (BS11) + metalaxyl MZ (0.25%) and TH1+ EA-2+ mancozeb (0.4%) in order. Pre-inoculation / pre-planting combined application of mustard cake, Vitex leaves and metalaxyl MZ also provided complete control both under pot and nursery conditions. Under orchard conditions, it increased the shoot length by 29.5 cm and restricted the collar rot lesion up 24.0 per cent. Amongst the combined applications of BCAs, bio-resources and fungicides, a mixed application of TH1, EA-2, mustard cakes and metalaxyl MZ exhibited complete control both under pot and nursery conditions, when applied before inoculation/ planting as well as their simultaneous application with target pathogen. Under orchard conditions, it increased the shoot length by 36.1 cm and restricted the collar rot lesion up to 32.1 percent. Replacing mustard cake in the above treatment either with Vitex leaf or bio-fumigation with mustard plants or botanical (Melia azedarach seed +Vitex leaf) cow urine decoction were also equally effective under orchard conditions (34.2-36.9 cm shoot length as against 6.1cm in untreated one). Integrating approach grafting with drenching of botanical cow urine decoction (10%) and metalaxyl MZ (0.25%) was most effective and increased the shoot length by 40.8 cm and healed the lesion up to 36.8%.